Use of Low-Molecular-Weight Heparin and Peak anti-Xa Monitoring In Severe SARS-CoV-2 Disease: A Brief Report. (December 2021) - Toor, Rebecca; Zamora, Francis J.; Fatteh, Naaz; Drexler, Nathan; Lozada, Jose
In 2019, a novel coronavirus was identified in Wuhan, China. This strain was classified as a pandemic in early 2020 by the World Health Organization (WHO), rapidly reaching millions of cases worldwide and overwhelming intensive care units. One distinct feature identified in severe SARS-CoV-2 is abnormal and complex coagulation and hematologic abnormalities, including significantly elevated D-dimer and fibrin/fibrinogen values possibly increasing morbidity and mortality in this patient population. Aggressive anticoagulation therapy with appropriate peak anti-Xa level monitoring has produce satisfactory results at our institution. Our intent is to present a case series of our strategy to highlight the benefits of this approach.